Coated-platelets predict stroke at 30 days following TIA. (11th July 2017) - Kirkpatrick, Angelia C.; Vincent, Andrea S.; Dale, George L.; Prodan, Calin I.
Abstract : Objective: To examine the potential for coated-platelets, a subset of highly procoagulant platelets observed on dual agonist stimulation with collagen and thrombin, for predicting stroke at 30 days in patients with TIA. Methods: Consecutive patients with TIA were enrolled and followed up prospectively. ABCD2 scores were obtained for each patient. Coated-platelet levels, reported as percent of cells converted to coated-platelets, were determined at baseline. The primary endpoint was the occurrence of stroke at 30 days. Receiver operator characteristic (ROC) analysis was used to calculate area under the curve (AUC) values for a model including coated-platelets to predict incident stroke at 30 days. Results: A total of 171 patients with TIA were enrolled, and 10 strokes were observed at 30 days. A cutoff of 51.1% for coated-platelet levels yielded a sensitivity of 0.80 (95% confidence interval [CI] 0.55–1.0), specificity of 0.73 (95% CI 0.66–0.80), positive predictive value of 0.16 (95% CI 0.06–0.26), and negative predictive value of 0.98 (95% CI 0.96–1.0). The adjusted hazard ratio of incident stroke in patients with coated-platelet levels ≥51.1% was 10.72 compared to those with levels <51.1%. ROC analysis showed significant improvement in the predictive ability of the coated-platelet model compared to ABCD2 score (AUC 0.78 ± 0.07 vs 0.54 ± 0.07, p = 0.01). Conclusions: These findings suggest a role for coated-platelets in risk stratification for stroke at 30 days after TIA.